Risk Analysis of The Raw Tofu Production Process with The FMEA Method at The Saudara Jaya Factory in Jember Regency - Sahari, Sindi Putri; Putra, Dhanang Eka (Politeknik Negeri Jember, 2024)
This study analyses the risk of tofu production at the Saudara Jaya Tofu Factory using the Failure Mode and Effect Analysis (FMEA) method with the aim of identifying potential failures and calculating the Risk Priority Number (RPN) value based on severity, frequency of occurrence, and detection. The results of the study found 17 risks in the tofu production process with 5 highest priority risks, namely the mixing of good and bad quality soya beans, improper dosage of vinegar, negligence in managing soaking time, inappropriate tofu size, and less dense tofu. To minimise these risks, several mitigation measures are proposed, including the selection of quality raw material suppliers, the use of soybean sorting machines, the creation of written SOPs, the use of timers for soaking, and the replacement of cutting tools and presses with more efficient ones. The implementation of these mitigations is expected to improve the quality and efficiency of tofu production as well as customer satisfaction.